Widening the zone of peri-implant attached gingiva. - (:unkn) unknown (My University, 1994)
The use of implant systems is a focus of interest nowadays, as an alternative method to classical dental prostheses used in partially or completely edentulous patients. Such an interest of both the patients and the clinicians seemed likely to be due to the opportunity of using fixed prostheses on these implants. However, besides its advantages, problems exist regarding the zone of attached gingiva around implants, for the vestibular depth has generally been decreased because of the excessive amount of alveolar bone resorption. The problem from the periodontal point of view is that the periodontal pockets around implants used as abutments may turn out to be pathologic pockets and an inadequate and nonfunctional vestibular depth will result. In this study, the conventional free soft tissue autograft technique was performed around 34 implants in 9 patients in whom 40 Brånemark implants in total were placed. The postoperative evaluations indicated that the decrease in the vestibular depth, due to the shrinkage of the keratinized tissue had a negative effect on this surgical procedure. The use of acrylic stents after surgery seemed to be a better solution and would give good clinical results.